The Digital Transformation of the Global Luxury Market - Sedláčková, Nicole Katarína; San José Iglesias, Rafael; Escobar Rios, Andrea; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor thesis examines how luxury brands, particularly in the fashion industry, are navigating digital transformation, with a focus on the balance between innovation and tradition. Using Hermès as a case study and drawing on insights from interviews with professionals and consumers of fashion brands, the research looks at how digital tools are shaping brand image, customer relationships, and purchasing behavior. The results show that while digital technologies offer new ways to reach customers and enhance their experience, they also challenge the exclusivity and craftsmanship that define luxury. The findings also identified Hermès as a brand that stands out for its careful and selective approach to digitalization, who embraces innovation while staying true to its heritage and artisanal values. This thesis explores how luxury fashion brands can embrace digitalization while staying true to their core values and identity, offering valuable insights into how brands can preserve their authenticity in today’s digital environment.
Vedoucí práce: Rafael San José Iglesias
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses